Challenging Thermodynamics: Hydrogenation of Benzene to 1, 3‐Cyclohexadiene by Ru@Pt Nanoparticles. Issue 1 (25th November 2016) - Weilhard, Andreas; Abarca, Gabriel; Viscardi, Janine; Prechtl, Martin H. G.; Scholten, Jackson D.; Bernardi, Fabiano; Baptista, Daniel L.; Dupont, Jairton
Abstract: Since the earliest reports on catalytic benzene hydrogenation, 1, 3‐cyclohexadiene and cyclohexene have been proposed as key intermediates. However, the former has never been obtained with remarkable selectivity. Herein, we report the first partial hydrogenation of benzene towards 1, 3‐cyclohexadiene under mild conditions in a catalytic biphasic system consisting of Ru@Pt nanoparticles (NPs) in ionic liquid (IL). The tandem reduction of [Ru(COD)(2‐methylallyl)2 ] (COD=1, 5‐cyclooctadiene) followed by decomposition of [Pt2 (dba)3 ] (dba=dibenzylideneacetone) in 1‐ n ‐butyl‐3‐methylimidazolium hexafluorophosphate (BMI⋅ PF6 ) IL under hydrogen affords core–shell Ru@Pt NPs of 2.9±0.2 nm. The hydrogenation of benzene (60 °C, 6 bar of H2 ) dissolved in n ‐heptane by these bimetallic NPs in BMI⋅ PF6 affords 1, 3‐cyclohexadiene with an unprecedented 21 % selectivity at 5 % benzene conversion. Conversely, almost no 1, 3‐cyclohexadiene was observed when using monometallic Pt 0 or Ru 0 NPs under the same reaction conditions and benzene conversions. This study reveals that the selectivity is related to synergetic effects of the bimetallic composition of the catalyst material as well as to the performance under biphasic reaction conditions. It is proposed that colloidal metal catalysts in ILs and under multiphase conditions ("dynamic asymmetric mixtures") can operate far from the thermodynamic equilibrium akin to chemically active membranes. Abstract : Thermodynamically unfavored : The first partial hydrogenation of benzene to 1, 3‐cyclohexadiene in a catalytic biphasic system (a "chemically active membrane‐like") composed of Ru@Pt nanoparticles in ionic liquid is reported.